Atividade antibacteriana, citotóxica e cicatrizante in vitro de fungos endofíticos isolados de plantas medicinais: Mimosa Tenuiflora (Willd.) Poir., Poincianella Pyramidalis Tul. e Acrocomia Aculeata (Jacq.) Lodd. Ex Mart. - Araújo, Joice Fragoso Oliveira de (2018)
Endophytic microorganisms inhabit the interior of plant tissues and live in mutuality with the host plant, and represent a rich and little studied source of new biologically active natural compounds. The present study aimed to evaluate the in vitro antibacterial, cytotoxic and healing activities of endophytic fungi isolated from the plant species Acrocomia aculeata, Poincianella pyramidalis and Mimosa tenuiflora. It was a basic in vitro experimental research with a quantitative approach. Initially, the fungi isolates were evaluated in culture and microscopy, and the extracts were obtained from three endophytic fungi Penicillium sp. (isolated from Poincianella pyramidalis), Rhizoctonia sp. (Mimosa tenuiflora isolate) and a fungi isolated from Acrocomia aculeata that was not identified. Minimal Inhibitory Concentration of extracts against Gram positive and Gram negative bacteria was determined by the Broth Microdilution Method, in addition to cytotoxic activity by Methyltetrazolium (MTT) colorimetric method with J774 macrophages and 3T3 fibroblasts and in vitro healing activity of Scratch Assay. In the antibacterial assay, extracts of Penicillium sp. and Rhizoctonia sp. showed no activity against the bacteria tested, while the extract of the fungus isolated from A. aculeata presented antibacterial activity against S. epidermidis and S. aureus. Regarding cytotoxic activity, the extracts tested were nontoxic at all concentrations in front of J774 macrophages, but in 3T3 fibroblasts Penicillium sp. and unidentified fungus isolated from A. aculeata were toxic at concentrations of 100 and 50 μg/mL, Rhizoctonia sp. showed no toxicity at any of the concentrations tested. As for in vitro healing activity, the extracts presented positive healing activity with a migration rate similar to the control. It was concluded that medicinal plants A. aculeata, P. pyramidalis and M. tenuiflora, harbor endophytic fungi with different pharmacological potentials, are Penicillium sp., Rhizoctonia sp. and an unidentified fungus isolated from A. aculeata, which requires the application of molecular techniques for its identification, and the latter has activity against S. epidermidis and S. aureus, as well as in vitro healing activity. The data obtained encourage further studies to determine the substances that contribute to evidenced activities in the present study, aiming at a possible therapeutic application.